KOMPARASI KEEFEKTIFAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) DAN TIPE THINK-PAIR-SHARE (TPS) PADA SISWA SMP (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2015)
This study aimed to get empirical evidence about the effectiveness of STAD and TPS cooperative learning on junior high school students’ achievement and interest in mathematics. This study was a quasi experimental research design with completely randomized factorial design. Sample were seventh grade students from two schools in Kebumen. The research instruments consisted of tests and interest questionnaire which contains questions and statement to determine the effectiveness of the learning model on students’ achievement and interest. The results showed that there was significant difference in achievement for STADA class (p = 0.046), STADB (p = 0.000), TPSA (p = 0.000), and TPSA (p = 0.042). In terms of interest, STAD and TPS significantly differed (p = 0.001, p
Keywords: pembelajaran kooperatif; STAD; TPS; prestasi; minat belajar matematika.; achievements; cooperative learning; interest in learning mathematic